Pracownia Teatru Tańca w Zielonej Górze - alternatywny obszar edukacji i animacji osób dorosłych = Dance Theatre Atelier in Zielona Góra - alternative area of adult education and animation - Zadłużny, Marek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The text is a result of the author?s reflexion on his own professional practice and especially on the contextual conceptualization of education and animation of adults implemented in the Dance Theatre Atelier in Zielona Góra. The article presents experiences of adult participants which are cognitively interesting from andragogical and animation perspective in the field of dance theatre. The considerations have been enriched with the author?s subjective narration as a pedagogue ? researcher, animator and choreographer of the group which allowed him to make an attempt to present undertaken issue from the autoethnographic perspective. In the text different contexts of participation in the Dance Theatre Atelier have been indicated referring to the statements of young and adult participants of classes as well as to their readings.
Keywords: teatr tańca; edukacja pozaformalna; edukacja nieformalna; autoetnografia; andragogika; dance theatre; non-formal education; informal education; autoethnography; andragogy